Facial mimicry, facial emotion recognition and alexithymia in post-traumatic stress disorder. (November 2019) - Passardi, Sandra; Peyk, Peter; Rufer, Michael; Wingenbach, Tanja S.H.; Pfaltz, Monique C.
Abstract: Individuals with post-traumatic stress disorder (PTSD) show abnormalities in higher-order emotional processes, including emotion regulation and recognition. However, automatic facial responses to observed facial emotion (facial mimicry) has not yet been investigated in PTSD. Furthermore, whereas deficits in facial emotion recognition have been reported, little is known about contributing factors. We thus investigated facial mimicry and potential effects of alexithymia and expressive suppression on facial emotion recognition in PTSD. Thirty-eight PTSD participants, 43 traumatized and 33 non-traumatized healthy controls completed questionnaires assessing alexithymia and expressive suppression. Facial electromyography was measured from the muscles zygomaticus major and corrugator supercilii during a facial emotion recognition task. Corrugator activity was increased in response to negative emotional expressions compared to zygomaticus activity and vice versa for positive emotions, but no significant group differences emerged. Individuals with PTSD reported greater expressive suppression and alexithymia than controls, but only levels of alexithymia predicted lower recognition of negative facial expressions. While automatic facial responses to observed facial emotion seem to be intact in PTSD, alexithymia, but not expressive suppression, plays an important role in facial emotion recognition of negative emotions. If replicated, future research should evaluate whether successful interventions for alexithymia improve facial emotion recognition abilities. Highlights: Automatic facial mimicry is intact in individuals with PTSD. Individuals with PTSD report greater expressive suppression than healthy controls. Individuals with PTSD are more alexithymic than healthy controls. Alexithymia predicts emotion recognition deficits in individuals with PTSD.